Girl with questioning eyes : a novel - Raghuwanshi, Neelesh; Deepa jain Singh (trn.) (Ranikhet Permanent Black, 2012)
This novel understands the soul of middle India like no other and shows it to us delicately and powerfully.
Keywords: IAS as an translator; Hindi fiction